ANALISIS METODE DAKWAH DALAM FILM AJARI AKU ISLAM KARYA DENI PUSUNG - Siti Annisa; Ali Nupiah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main problem in this study is what methods of preaching are displayed in the film Ajari Aku Islam by Deni Pusung according to the methods of preaching contained in the An-Nahl verse 125, namely the bil-hikmah method, mau'izah al hasanah and Mujadalah al-Lati Hiya Ahsan. The purpose of this discussion is to find out how the methods of preaching are displayed in the film Ajari Aku Islam. This type of research is by using qualitative research, where in this research the data analysis approach is carried out with the content analysis method. The techniques used are two, literature study, documentation. The data obtained will later be classified based on the dialogue, to then reduce the data, so that it can be presented and conclusions drawn. Based on the research conducted by the author, it can be concluded that there are fifteen methods of preaching shown in the film Ajari Aku Islam. First, there are six scenes containing the bil-hikmah method in the film Ajari Aku Islam. Second, the mauÔÇÖizah al hasanah method is found in five scenes in the film Ajari Aku Islam. Third, there are four scenes containing the Mujadalah al-Lati Hiya Ahsan method in the film Ajari Aku Islam.